Managing issues on risk management implementation among sub contractors in northern area / Nurqameela Md Radzi, Kartina Alauddin and Mohmad Mohd Derus - Md Radzi, Nurqameela; Alauddin, Kartina; Mohd Derus, Mohmad (2021)
The construction industry is known as a high-risk activity as their work of nature. The risk should be managed crucially by any level of multidiscipline. Construction activities involved with hazard situations and an unpredictable incident during construction. This would contribute to the failure or delay in the projects. There is a main issue triggered by sub-contractors tasks, i.e. failure to manage effectively the risk management provided by main contractors. There are many factors thatcontributed to the ineffective risk management implementation among sub-contractors, including lack of skills and expertise, lack of experience, and communication breakdown with the team. This situation reflected the main contractor responsibilities to the client. Hence, this paper aims to assist sub-contractors to overcome this situation. Therefore, this study has developed two (2) objectives. First, to identify the factors that contribute to ineffective implementation among Sub-Contractors. Next, to propose the strategy to overcome the ineffective implementation of risk management. The research methodology adopted was the online questionnaire survey analysis based on 120 respondents from selected sub-contractors among G1 to G4 in thenorthern state of East Malaysia. Findings indicated that there are a number of sub-contractors agreed that lack of knowledge, communication issues among parties involved and frequent design changes are among the factors causing ineffective risk management. To improve the effectiveness of risk management among sub-contractors, this study suggests that there must be enforcement of strategies and guidelines on sub-contractors' activities and responsibilities.